2023
DOI: 10.23863/kalem.2022.228
|View full text |Cite
|
Sign up to set email alerts
|

Cebir Öğretiminde Gerçekçi Matematik Eğitimi Yaklaşımının Öğrenci Başarısına ve Kalıcılığına Etkisi

Abstract: Bu araştırmanın amacı Gerçekçi Matematik Eğitimi ile 6. sınıf cebir öğretiminin, öğrencilerin akademik başarılarına ve kalıcılığa etkisini incelemektir. Araştırmada öntest-son test deney ve kontrol gruplu yarı deneysel desen kullanılmıştır. Çalışma, Bursa ilinde bulunan iki devlet ortaokulunda, 20 kişi deney ve 24 kişi de kontrol grubu olmak üzere 44 altıncı sınıf öğrencisiyle yürütülmüştür. Araştırmanın örneklemi rastgele örnekleme yöntemi kullanılarak oluşturulmuştur. Dersler, “Cebir” öğrenme alanında deney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Accordingly, it could be concluded that the students' skills in associating mathematics with real-life improved significantly as a result of the application. It was possible to mention that some studies analyzing the effect of Realistic Mathematics Education on mathematics achievement also supported this result, and studies conducted with activities based on Realistic Mathematics Education achieved successful results in increasing mathematics achievement (Akkaya, 2019;Bintaş et al, 2003;Gelibolu, 2008;İnce, 2019;Klein et al, 1998;Özdemir & Üzel, 2011;Özdemir, 2020;Özkan et al, 2023;Widjaja & Heck, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…Accordingly, it could be concluded that the students' skills in associating mathematics with real-life improved significantly as a result of the application. It was possible to mention that some studies analyzing the effect of Realistic Mathematics Education on mathematics achievement also supported this result, and studies conducted with activities based on Realistic Mathematics Education achieved successful results in increasing mathematics achievement (Akkaya, 2019;Bintaş et al, 2003;Gelibolu, 2008;İnce, 2019;Klein et al, 1998;Özdemir & Üzel, 2011;Özdemir, 2020;Özkan et al, 2023;Widjaja & Heck, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…When the literature is examined, it is seen that there are studies examining the effect of GME on students' academic achievement at the primary school level. Can (2012) taught the 3rd-grade Measuring Liquids and Lengths topic based on GME. As a result of his study, Can (2012) determined that GME is effective in increasing students' academic achievement, similar to the results of this study.…”
Section: Gme Digital Stories and Mathematics Achievementmentioning
confidence: 99%
“…Can (2012) taught the 3rd-grade Measuring Liquids and Lengths topic based on GME. As a result of his study, Can (2012) determined that GME is effective in increasing students' academic achievement, similar to the results of this study. Çakır (2013) also stated in their study that GME positively affects students' achievement in teaching topics in the 4th-grade measurement learning area.…”
Section: Gme Digital Stories and Mathematics Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırmada elde edilen bulgular literatürdeki benzer çalışmalarla birlikte değerlendirildiğinde ulaşılan sonuçlar bu bölümde verilmiştir. Bu araştırmada sadece "doğal sayılarda toplama ve çıkarma işlemi problemleri" öğretiminin yapılması çalışmanın sınırlılıklarındandır ve ilkokul düzeyinde yapılan çalışmalar (Altunay, 2018;Aydın, 2014;Can, 2012;Çilingir, 2015;Uskun vd., 2020) incelendiğinde GME ders planlarıyla yapılan öğretimin ilkokulun farklı sınıf düzeylerinde, farklı öğrenme alanlarında, uzun dönemli ve boylamsal etkilerinin farklı yöntemlerle birlikte incelenmesi tavsiye edilmektedir.…”
Section: Tartişma Ve Sonuçunclassified